Left ventricular diastolic dysfunction in HIV-uninfected infants exposed in utero to antiretroviral therapy. (15th March 2020) - Lipshultz, Steven E.; Sasaki, Nao; Thompson, Bruce; Eidem, Benjamin W.; Cheng, Irene; Colan, Steven D.; O'Brien, Sharon E.; Amdani, Shahnawaz; Shearer, William T.; Orav, Endel John; Miller, Tracie L.; Wilkinson, James D.
Abstract : Objectives: To longitudinally measure LV diastolic function in HIV-exposed but uninfected (HEU) children perinatally exposed to ART. Design: HEU children who were perinatally exposed to antiretroviral therapy (ART) may be at risk for adverse cardiac effects. We have previously reported that those children have decreased left ventricular (LV) mass, dimension, and septal thickness with increased contractility. Methods: Serial echocardiograms were obtained at specific times from birth to 48 months from two groups of HIV-uninfected children: 148 HIV-negative children who were perinatally exposed to ART and 130 non-ART-exposed HIV-unexposed healthy controls. The following LV diastolic indices were obtained: mitral valve early and late diastolic velocity ( E and A ), tissue Doppler-derived LV-free wall and septal early diastolic velocity (LV e ′ and sep e ′). Results: All echocardiographic indices were significantly different in ART-exposed children compared with ART-unexposed healthy controls. Both E and A were overall lower at all ages by 8.28 cm/s ( P  = 0.0002) and 13.46 cm/s ( P  < 0.0001) respectively. E / A ratio was higher by 0.27, 0.46, and 0.28 units at birth, 1 year and 2 years of age, respectively (all P  ⩽ 0.01). Moreover, LV e′ and sep e′ were overall lower at all ages by 0.84 cm/s ( P  = 0.01) and 0.47 cm/s ( P  = 0.02), respectively. Conclusion: Children who were exposed to ART in utero have subclinical yet significant differences in specific LV diastolic indices. Follow-up with serial echocardiograms are recommended in this population to further assess the potential cardiac toxicity of perinatal exposure to ART.